Evaluasi Faktor yang Berpengaruh pada Kinerja Karyawan - Harmon Chaniago (Asosiasi Ahli Administrasi Indonesia, 2020)
This research was conducted at companies whose employee performance was decreasing. This is evidenced by the number of employees who can only work individually and do not want to work as a team. The results of the initial observations show the influence of several factors on employee performance. This study aims to investigate these factors, such as: job stress, work conflict, satisfaction, work comfort and its associated with employee performance. The research method uses an explanatory survey. The number of samples used was 120 property company employees in West Bandung Regency, Indonesia. The results of the study indicate that job stress, work conflict, job satisfaction and work comfort have an effect on improving employee performance, while the most dominant factor affecting employee performance is work comfort.